Contemporary approaches in prevention of sudden cardiac death - Kostic, Tomislav; Deljanin-Ilić, Marina; Stanojevic, Dragana; Milic, Dragan; Koracevic, Goran; Apostolovic, Svetlana; Perisic, Zoran; Salinger-Martinovic, Sonja; Djordjevic, Miodrag; Golubovic, Mladjan; Lazarevic, Milan (Acta medicae Medianae, 2021)
Sudden cardiac arrest and sudden cardiac death (SCD) are terms that are often used in medicine as synonyms. Sudden cardiac death is defined as "natural, unexpected cardiac death that occurs within one hour of the onset of acute symptoms and is accompanied by a sudden loss of consciousness." The presence of heart disease may be known from before, but the timing and manner of death are unexpected. Coronary artery disease (CAD) is responsible for 75-80% of all SCD. While atherosclerosis is a primary disease in middle-aged and elderly people, in children and young adults (
Keywords: sudden cardiac death, primary and secondary prevention, implantable cardioverter defibrillator